Hands-On IoT Solutions with Blockchain : Discover How Converging IoT and Blockchain Can Help You Build Effective Solutions. - Santos, Maximiliano (Packt Publishing Ltd, 2019)
IoT and Blockchain are not limited to certain industries or use cases. Almost any business with a network and IoT device can reduce costs, improve business efficiency, and remove single points of failure in networks by implementing Blockchain. This book will help you implement an end-to-end Blockchain and IoT solution using best practices.